Taysīr al-Qirāʾāt al-Qurʾāniyyah fī Sulṭanat Brunāy Dār al-Salām - Al-Khateri, Saeed Abdullah Saeed; Mokhtar, Ahmad Baha Bin Haji; Lazim, Khairun Naqibah binti Haji (Al-Zahra: Journal for Islamic and Arabic Studies, 2024)
In the current era, many students encounter challenges in understanding the science of Qur'anic readings due to the complexity of its terms, symbols, methods, and narrations. This has led to a noticeable preoccupation with the subject, impacting both the discipline and its teaching institutions. Recognizing this issue, the study explores the reasons behind these difficulties and proposes mechanisms to simplify and enhance accessibility for learners. Focusing on the context of the Sultanate of Brunei, the study aims to assess the current state of Qur'anic readings and offer practical solutions to improve teaching and learning. Using a descriptive, analytical, and field-based approach, the researchers collected and categorized data through dialogues with students and specialists. The data were analyzed to develop recommendations aligned with the study’s objectives. The findings highlight that facilitating the science of Qur'anic readings remains an open field, requiring further innovation and research. Suggestions include using mind maps, teaching students to write the Qur'an with the ten canonical narrations, and other strategies detailed in the study. These efforts aim to advance the study of this noble science and make it more accessible to learners.